The impact of social media on social habits in the UAE family Under coronavirus pandemic - AlMazrouei, Sultan; Mostafa, Zezit (Al-Adab Journal, 2023)
This research examined the impact of social media on social habits in the UAE family in light of the coronavirus pandemic. Such as modifying them for hospitality and visiting habits, as well as marriage habits, was based on the analytical descriptive curriculum, and was based on a measure aimed at knowing this impact, through the study community, institutions in the Kalba region of the United Arab Emirates, the sample consisted of 400 municipal workers, the Department of Social Services and a number of educational institutions. This research found that social media played an important role in communication between individuals under the pandemic, and in congratulations and blessings. In addition to the impact of the epidemic on the family’s financial and social aspects and on the confinement of marriage to family parties, which has contributed to reducing the costs of marriage, the researcher recommended that the epidemic commit itself to changing habits such as lack of opulence and discretion in marriage parties, and that such means should be monitored to prevent their use in spreading false news.